2016
DOI: 10.1007/s00705-015-2744-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of full-length genomes of porcine teschovirus (PTV) and the effect of purifying selection on phylogenetic trees

Abstract: To study the outcome of natural selection using phylogenetic trees, we analyzed full-length genome sequences of porcine teschovirus (PTV). PTV belongs to the family Picornaviridae and has a positive-stranded RNA genome, the replication of which is carried out by the error-prone viral RNA-dependent RNA polymerase. The viral RNA encodes a single polyprotein that is cleaved into structural (i.e., L, VP4, VP2, VP3 and VP1) and nonstructural proteins (i.e., 2A, 2B, 2C, 3A, 3B, and 3C). A high degree of genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Notably, some PTVs showed phylogenetic incompatibility among different structural protein regions, which was significantly correlated with the multiple, complex recombination events in the evolutionary history (data not shown). A previous study demonstrated a signature of strong purifying selection in PTVs, suggesting that most amino acid mutations were the result of genetic drift (Villanova et al, 2016). In the present study, selection pressure analyses in all 72 non-recombinant PTVs revealed only two sites under positive selection by means of three methods, at codon 2 (L 2 ) and codon 120 (VP4 34 ); sites 23 and 29 in the leader protein were detected to be positively selected by two methods; and the other six amino acid substitutions were identified to be positively selected by at least one method.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, some PTVs showed phylogenetic incompatibility among different structural protein regions, which was significantly correlated with the multiple, complex recombination events in the evolutionary history (data not shown). A previous study demonstrated a signature of strong purifying selection in PTVs, suggesting that most amino acid mutations were the result of genetic drift (Villanova et al, 2016). In the present study, selection pressure analyses in all 72 non-recombinant PTVs revealed only two sites under positive selection by means of three methods, at codon 2 (L 2 ) and codon 120 (VP4 34 ); sites 23 and 29 in the leader protein were detected to be positively selected by two methods; and the other six amino acid substitutions were identified to be positively selected by at least one method.…”
Section: )mentioning
confidence: 99%
“…Porcine teschovirus (PTV) in the genus Teschovirus within the family Picornaviridae is a non‐enveloped virus with a single‐stranded RNA genome of positive polarity (ICTV, ). PTV has a genome of about 7.1 kb containing a single long open reading frame (ORF) on the viral RNA that is processed to form 12 individual mature proteins, comprising a leader (L) protein followed by the viral capsid proteins, four structural proteins (VP1–4), and seven non‐structural proteins (2A–C, 3A–D) (Cano‐Gómez & Jiménez‐Clavero, ; Villanova, Cui, Ai, & Leal, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sequences were selected basically by the absence of recombination. Recombinant strains need to be removed because recombination is a significant bias to the inferences of trees based on maximum likelihood or Bayesian approaches [31]. The presence of positive selection was also measured in the alignments of VP2 in order to contemplate the effect of positive selection on the topology of the trees.…”
Section: Ancestral Reconstruction Of Amino Acids Of Vp2 In Carnivoroumentioning
confidence: 99%
“…The diversity of carnivore protoparvoviruses has been described in many studies and seems to be represented by a great variety of strains and recombinant forms [27,[30][31][32]. Conversely, there are few studies describing the heterogeneity of FPLV strains and its relevance to the maintenance of these viruses in distinct hosts [13].…”
Section: Introductionmentioning
confidence: 99%